Epistemic modality and deontic modality at the crossroads - Jumino Suhadi (Proceedings of AICS - Social Sciences, 2013)
This article is a descriptive survey on the similarities and differences between epistemic and deontic modalities as introduced by Halliday (1994: ) and Downing and Locke (199: 283) . Epistemic modality refers to the use of modality which is based on the speaker's evaluation and judgment in relation to the degree of confidence of the knowledge on the proposition. It functions to comment on and evaluate an interpretation of reality in carrying out speech functions. Deontic modality indicates whether the proposition expressed by a command is obligatory, advisable or permissible according to some normative background such as law, morality, convention, etc. In many instances, the meanings of some modals are relative and complements to each other.  The evidence of some extrinsic modalities such as must, should, may, and can indicates that they may fall under different types; thus, they are at the crossroads; two types of modality which may use the same realization but they goes to different meanings.Keywords:Systemic Functional Linguistics, epistemic modality, deontic modality